2014
DOI: 10.7250/ste.2014.001
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management – a Neglected Dimension in Discourse on Safety Management and Safety Culture – Evidence from Estonia

Abstract: Abstract. The current study proposes a model for a positive safety culture with a knowledge management dimension and tests this on a sample of 1757 employees from Estonian SMEs in different branches of industry, using the factor analysis. Despite conceptual and empirical justification, researchers have not consistently included concepts of knowledge management in safety culture studies. This paper explores the possibility of using Knowledge Management in the Occupational Health and Safety Management System. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Despite these limitations, this study has revealed findings that have both theoretical and practical significance. The implications that these findings have for both safety culture and organizational science research are of particular importance [24]. From a more practical standpoint, it is likely that senior managers can benefit from a balanced approach to safety that includes traditional safety management activities (i.e., management of physical or tangible resources/ assets, such as safer technology, regular audits, hazard identification, proper risk assessment; use of less hazardous chemicals and the elaboration of safe procedures, safety policies and guidelines etc.…”
Section: Limitationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite these limitations, this study has revealed findings that have both theoretical and practical significance. The implications that these findings have for both safety culture and organizational science research are of particular importance [24]. From a more practical standpoint, it is likely that senior managers can benefit from a balanced approach to safety that includes traditional safety management activities (i.e., management of physical or tangible resources/ assets, such as safer technology, regular audits, hazard identification, proper risk assessment; use of less hazardous chemicals and the elaboration of safe procedures, safety policies and guidelines etc.…”
Section: Limitationsmentioning
confidence: 99%
“…This article examines relationships between a safety climate and a safety culture, tests an innovative conceptual safety culture model proposed in previous research [24], based on employers' responses. Focus is given on organizational safety culture and the structure or architecture of employees' and employers' attitudes to safety as part of that culture, as well as the ability to learn, which also should mean changes in employees' behavior in order to enhance safety culture.…”
Section: Safety Of Technogenic Environmentmentioning
confidence: 99%
See 3 more Smart Citations